THE ANALYSIS OF STUDENTS’ DIFFICULTIES AND FACTOR OF USING MEDIA NETFLIX FOR LISTENING LEARNING AT ELEVEN GRADE OF SMAN 9 BANDAR LAMPUNG - Muhammad Alfu Syahrin; Yanuarius Yanu Dharmawan (Universitas Bandar Lampung, 2022)
The purpose of this study was to describe the difficulties and factors of students when using Netflix, especially in listening learning skills. By using the qualitative method, data collection is done by means of questionnaires and interviews. As many as 30 students who use Netflix were selected to be participants from all 11th grade of science and social studies majors. Limited vocabulary, quality of recorded material, accent, speaking speed, and physical factors are the main listening learning problems faced by students at SMAN 9 Bandar Lampung. The services offered by the Netflix platform are of the best quality compared to other platforms, even though the price given is not suitable for students, but this is not a big problem for them. For them, the biggest difficulty is when they understand the material presented, there is something they don't understand and there is no teacher to explain it.